Cost and benefit analysis of waste management at Rawa Kucing landfill with the refuse-derived fuel (RDF) method - Zahra, Nabila Fathia; Sari, Pepy Hapita (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study addresses the complex challenges of waste management at Indonesia's Rawa Kucing landfill, highlighting the need for sustainable solutions such as Refuse- Derived Fuel RDF) to reduce reliance on landfills and address gas emissions. Ineffective waste management, environmental pollution, and limited infrastructure reinforce the urgency for methods that can effectively reduce waste volumes and promote renewable energy. This study aims to evaluate the feasibility of RDF in waste management by assessing the economic, environmental, and health benefits. Methods: Using circular economy theory and cost- benefit analysis (CBA), RDF was assessed for its potential in carbon reduction, renewable energy production, and sustainability. Findings: Findings show significant benefits of the RDF in reducing waste in landfills, improving management efficiency, and providing alternative energy sources. Economic benefits, such as revenue from RDF sales, and environmental benefits in the form of reduced greenhouse gas emissions are particularly important. addition, RDF can reduce health risks by lowering pollution from well-managed waste piles. RDF is proven to be an effective and economically beneficial waste management alternative to conventional methods. Conclusions: This study recommends expanding the adoption of RDF in various landfills in Indonesia as well as increasing public awareness on the benefits of RDF. Novelty/Originality of this Article: This research offers a novel approach by combining circular economy theory with cost-benefit analysis (CBA) to evaluate the multiple benefits of RDF, not only in waste reduction and energy production, but also in improving public health.